Explosion parameters and combustion kinetics of biomass dust. (December 2019) - Liu, Aihua; Chen, Jieyun; Huang, Xiaofei; Lin, Junjiang; Zhang, Xiaochun; Xu, Wenbin
Graphical abstract: Highlights: Explosion hazard level: dalbergia cochinchinensis > cupressus funebris > pine sawdust. Combustion behavior of biomass at three different heating rates was observed. Different kinetic models were used to investigate apparent activation energy ( Eα ). The main gas products of biomass are CO2, CO, CH3 COOH, and H2 O. Volatile matter content of biomass is predictable via its explosion hazard. Abstract: In this study, a 20-L spherical explosion vessel, hot plate apparatus, Godbert-Greenwald furnace apparatus, and TG-FTIR were used to investigate the explosion and combustion characteristics of three biomass dusts: dalbergia cochinchinensis (DC), pine sawdust (PS), and cupressus funebris (CF). DC with lower minimum explosible concentration (70–80 g/m 3 ), larger maximum explosion pressure (0.742 MPa) and larger maximum explosion pressure rise rate (80.14 MPa/s) had the greatest explosion hazard in three biomass dusts. The apparent activation energy of DC and CF were lower than that of PS, and the main gas products of three samples included CO2, CO, CH3 COOH, and H2 O. The volatile matter content of DC characterized by the weight loss and the number of gas products of combustion process was higher than those of PS and CF, showing that the volatile matter content of biomass dust was one of the main factors affecting combustion and explosion hazard.